The good wife. The fifth season [videorecording (DVD)] - Margulies, Julianna, 1966-; Baranski, Christine; Cumming, Alan, 1965-; Charles, Josh, 1971-; Noth, Chris, 1954-; Czuchry, Matt, 1977-; Panjabi, Archie
Alicia Florrick and Cary join forces to launch their own law firm. As they sever ties with Lockhart/Gardner, tensions escalate and explode as the new rivals go into attack mode, battling each other both in and out of court. Alicia's new venture leads her to volatile showdowns, altering every major relationship she's cultivated. Season five witnesses Alicia's complete transformation from a good wife to a legal powerhouse.